(untitled) (Pedagogy of Higher and Secondary Education, 2003)
In the article is concretized such conception “climate”, “activity” and the characteristic is given for active-creative climate, the meaning of creation ih live creative climate at the methodic lectures is reveated, the process of creating the work, the teachers results of creative group auproposed and checked.